How career adaptability influences job embeddedness of self-initiated expatriates? The mediating role of job crafting - Mustafa AlMemari; Khalizani Khalid; Abdullah Osman (Cogent Business & Management, 2023)
The purpose of this study was to examine the relationship between career adaptability, job crafting, and job embeddedness, and it was predicted that career adaptability promotes job embeddedness in self-initiated expatriates by increasing their job crafting behavior. Data were collected from 881 self-initiated expatriates from multinational companies in the United Arab Emirates, which were analyzed using structural equation modeling. The structural equation modeling results support the proposed hypotheses and suggest that career adaptability and job crafting are associated with job embeddedness. Specifically, career adaptability is effective in promoting job embeddedness through job crafting. Therefore, career adaptability is an important antecedent for self-initiated proactivity and job embeddedness in organizations.
Keywords: M14; J24; J28; M54; 650; United Arab Emirates; career adaptability; job crafting; job embeddedness; self-initiated expatriate